Optimized Treatment Strategies for Naturally Occurring Radioactive Materials (NORM) in Iraqi Oil and Gas Operations - M. W. Alhamd; Ahmed Saddam Mola; Mazen Katea Al-Gharrawy; Zaki Abduljabbar Alqaisi (Iraqi Journal of Industrial Research)
Naturally Occurring Radioactive Materials (NORM) in the oil and gas industry pose significant environmental and health challenges. During extraction and production, radionuclides such as radium-226, radium-228, uranium-238, polonium-210, and lead-210 accumulate in equipment, pipelines, and sludge, forming Technologically Enhanced Naturally Occurring Radioactive Materials (TENORM). Exposure to these radioactive contaminants can increase health risks for workers and complicate waste management. This study evaluates the effectiveness of an integrated remediation process combining thermal, chemical, and detergent-based treatments to reduce NORM contamination. Experimental procedures involved heating contaminated samples to 800°C, applying phosphoric acid to dissolve radioactive scales, and using chlorine-based detergents to facilitate radionuclide removal. The decontamination efficiency was assessed by measuring radionuclide concentrations before and after treatment using gamma spectroscopy. Results showed that acid leaching reduced uranium-238 by 64% and radium-226 by 56%, while detergent application further decreased radium-226 by 99.4%, lowering it from 700,000 Bq/kg to 4,000 Bq/kg. The final step, liquid evaporation, achieved a 99.98% reduction, with radium-226 levels dropping to 500 Bq/kg. These findings highlight the importance of a multi-step remediation approach for effectively managing NORM waste. The proposed treatment strategy provides a practical and scalable solution for reducing radiation hazards in oil and gas operations, supporting worker safety and environmental protection while aligning with international regulatory standards.